2023
DOI: 10.3389/fonc.2023.1126550
|View full text |Cite
|
Sign up to set email alerts
|

Specific gene expression signatures of low grade meningiomas

Abstract: IntroductionMeningiomas are the most common primary central nervous system (CNS) tumors in adults, representing approximately one-third of all primary adult CNS tumors. Although several recent publications have proposed alternative grading systems of meningiomas that incorporate genomic and/or epigenomic data to better predict meningioma recurrence and progression-free survival, our understanding of driving forces of meningioma development is still limited.ObjectiveTo define gene expression signatures of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Recent developments in genomics have led to further stratification of meningioma subtypes based on alterations in somatic gene copy numbers and genome-wide profiling of DNA methylation [20,40,41]. Patel et al combined whole-genome sequencing and transcriptome analysis and suggested the classification of meningiomas into three major types: type A includes missense mutations in TRAF7, KLF4, and AKT1 and has minimal chromosomal alterations [42], similar to previous findings in benign meningiomas [40]; type B includes NF2-deficient non-aggressive meningiomas; and type C includes more aggressive meningiomas, which have a significant chromosomal instability and chromosomal gains and losses, most commonly losses of both chr22q and chr1p [42]. Using these molecular principles, Tsitsikov et al compared transcriptional profiles of four of the most common benign types of meningiomas: (1) NF2 loss versus meningiomas with TRAF7 missense mutations, (2) NF2 tumors with or without additional loss of chr1p, and (3) TRAF7 meningiomas with additional missense mutations in AKT1 or KLF4.…”
Section: Grading Of Meningiomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments in genomics have led to further stratification of meningioma subtypes based on alterations in somatic gene copy numbers and genome-wide profiling of DNA methylation [20,40,41]. Patel et al combined whole-genome sequencing and transcriptome analysis and suggested the classification of meningiomas into three major types: type A includes missense mutations in TRAF7, KLF4, and AKT1 and has minimal chromosomal alterations [42], similar to previous findings in benign meningiomas [40]; type B includes NF2-deficient non-aggressive meningiomas; and type C includes more aggressive meningiomas, which have a significant chromosomal instability and chromosomal gains and losses, most commonly losses of both chr22q and chr1p [42]. Using these molecular principles, Tsitsikov et al compared transcriptional profiles of four of the most common benign types of meningiomas: (1) NF2 loss versus meningiomas with TRAF7 missense mutations, (2) NF2 tumors with or without additional loss of chr1p, and (3) TRAF7 meningiomas with additional missense mutations in AKT1 or KLF4.…”
Section: Grading Of Meningiomasmentioning
confidence: 99%
“…Using these molecular principles, Tsitsikov et al compared transcriptional profiles of four of the most common benign types of meningiomas: (1) NF2 loss versus meningiomas with TRAF7 missense mutations, (2) NF2 tumors with or without additional loss of chr1p, and (3) TRAF7 meningiomas with additional missense mutations in AKT1 or KLF4. Their analysis showed distinct transcriptional programs specific for each meningioma genotype [40]. Other studies have integrated multiple parameters, including DNA methylation, RNA-seq, and cytogenetic profiling to enhance the grading of meningiomas [43,44].…”
Section: Grading Of Meningiomasmentioning
confidence: 99%
“…Recent developments in genomics have led to further stratification of meningioma subtypes based on alterations in somatic gene copy numbers and genome-wide profiling of DNA methylation [20,39,40]. Patel et al combined whole genome sequencing and transcriptome analysis and suggested another classification of meningiomas into 3 major types: type A have missense mutations in TRAF7, KLF4, and AKT1 and have minimal chromosomal alterations [41], similar to previous findings in benign meningiomas [39]; type B are NF2-deficient non-aggressive meningiomas; and type C are more aggressive meningiomas which have a significant chromosomal instability and chromosomal gains and losses, most commonly loss of both chr22q and chr1p [41]. Using these molecular principles, Tsitsikov et al compared transcriptional profiles of four of the most common benign types of meningiomas: 1) NF2 loss versus meningiomas with TRAF7 missense mutations, 2) NF2 tumors with or without additional loss of chr1p, 3).…”
Section: Grading Of Meningiomasmentioning
confidence: 99%
“…TRAF7 meningiomas with additional missense mutations in AKT1 or KLF4. Their analysis showed distinct transcriptional programs specific for each meningioma genotype [39]. Other studies have integrated multiple parameters, including DNA methylation, RNA-seq, and cytogenetic profiling to enhance the grading of meningiomas [42,43].…”
Section: Grading Of Meningiomasmentioning
confidence: 99%